Effect of E-learning clinical management of substance-dependent pregnant women on the knowledge and clinical skill performance of midwives: a randomized controlled trial - Hasti Heidarian; Manoosh Mehrabi; Parvin Ghaemmaghami; Roksana Janghorban (BMC Pregnancy and Childbirth)
Abstract Background Drug use during pregnancy and post-partum undoubtedly significantly affects maternal and infant morbidity. Healthcare providers, especially midwives who care for pregnant and postpartum women, must possess adequate knowledge and clinical skills to manage their patients appropriately. This study aimed to determine the effect of an e-learning intervention on midwives’ knowledge and clinical performance skills in caring for substance-dependent pregnant women during labor and post-partum. Methods A randomized controlled trial based on e-learning was conducted in Shiraz, Iran. One hundred midwives working in governmental maternity hospitals were recruited and randomly assigned to the intervention (n = 50) or control (n = 50) group through blocked randomization. The intervention group underwent e-learning for 4 weeks on clinical considerations during labor and post-partum of substance-dependent mothers. The control group received no educational intervention from the research group. Pre-test, post-test, and one-month retention tests included a knowledge assessment questionnaire and an objective structured clinical examination test to assess clinical skill performance in both groups. The data were analyzed using SPSS 16 software at a significance level of P < .05. Analysis of variance with repeated measures was used to compare the mean data between and within the groups. Results A total of 93 midwives with a mean age of 36.78 ± 8.06 years were recruited and randomly assigned to the control group (n = 47) and the intervention group (n = 46). Seven midwives dropped out for different reasons. Immediately after and one month after the intervention, both the level of knowledge and the level of clinical skill performance of the midwives in the intervention group increased compared to those before the intervention (P < .001) and compared to those in the control group (P < .001). The knowledge of the intervention group in the one-month retention test was significantly reduced compared to that immediately after the intervention (P < .001), but clinical skill performance in the intervention group at one month after the intervention was not significantly different from that immediately after the intervention (P = 1.00). Conclusions E-learning about clinical considerations during labor and post-partum in substance-dependent mothers can be an effective way to improve midwives’ knowledge and clinical skill performance. Although knowledge decreased one month after training, clinical skill performance improved. Trial Registration http://www.irct.ir/ , IRCT20180928041164N1 registered November 13, 2018.